Agua y procesos de educación ambiental en Bogotá - Hernández Gómez, Carmen Alicia; Vargas Aldana, Claudia María (Educación y Ciudad, 2020)
In this research article, we describe with actor-network theory, the environmental education practices about water in different scenarios in Bogotá: education programs from the Secretary of the Environment, school institutions, and the work of social organizations. The ontoepistemic description that we propose involves three agency nodes: the concept of water, teaching strategies, and pedagogical meanings. These nodes indicate the particularities that the teaching of water acquires in formal and non-formal spaces, as well as its connections and collaborations